2009
DOI: 10.2174/1874213000902010100
|View full text |Cite
|
Sign up to set email alerts
|

Balancing the Size-Number Tradeoff in Clonal Broods

Abstract: Abstract:The trade-off between the number of offspring in a brood and the sizes of those offspring has been documented in a diverse array of species. Here we consider the factors that might account for the way that the trade-off achieves a particular size-number balance for female offspring. In particular, we determine whether bet hedging, along with traits influencing the expected short-term reproductive success of the brood, could select for a brood size and body mass that maximize long-term fitness. We also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 41 publications
(53 reference statements)
1
6
0
Order By: Relevance
“…). This pattern is consistent with a recent modelling analysis based on C. bakeri (Crowley & Saeki ), under conditions in which fitness benefits from larger body mass and larger brood size accrue with diminishing returns. Note in Fig.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…). This pattern is consistent with a recent modelling analysis based on C. bakeri (Crowley & Saeki ), under conditions in which fitness benefits from larger body mass and larger brood size accrue with diminishing returns. Note in Fig.…”
Section: Discussionsupporting
confidence: 91%
“…; Stuefer, van Hulzen & During ). Two possible adaptive explanations for larger brood size combined with smaller body mass in response to the poorer nutritional environment are as follows: (i) Poor nutritional conditions may signal the need for greater emphasis on bet hedging, in which larger broods can help reduce the variance in brood reproductive success and thus increase lineage fitness (Crowley & Saeki ); (ii) Increasing brood size under poor nutritional conditions may help ensure survival of the brood during wasp larval development.…”
Section: Discussionmentioning
confidence: 99%
“…In parasitoids and other similar organisms, the single host constrains the resources for development (even in koinobionts), and hence the maximum adult body size. In gregarious parasitoids, there is the additional constraint of dividing the host resources across the rest of the developing brood (Mayhew & Glaizot, ; Crowley & Saeki, ). Hence, a trade‐off between offspring size and number is expected after accounting for the size of the host (Hardy et al., ), whereas a positive correlation between parasitoid body size and host body size is expected, especially in solitary species.…”
Section: Trade‐offsmentioning
confidence: 99%
“…1. An example of each tradeoff component, based on studies of a parasitoid wasp exploiting its host (Saeki et al 2009, Crowley and Saeki 2009, Saeki and Crowley 2012, 2013), is shown to the right of each component. The constraint is the amount or supply rate of the limiting resource (e.g.…”
Section: Definitions and Logicmentioning
confidence: 99%
“…For example, in the progeny size-number tradeoff when the mother controls the allocation, she optimizes individual offspring mass and total number within a finite total mass (Saeki andCrowley 2012, 2013). The role of selection was addressed in a preliminary model (Crowley and Saeki 2009) and is the focus of work in progress (PHC, Paul Ode and Éric Wajnberg). The tradeoff relationships are convex and statistically consistent with the multiplicative relationship between trait magnitudes.…”
Section: Magnitude Of Traitmentioning
confidence: 99%